Unconscious perception of one's own name modulates amplitude of the P3B ERP component. (October 2020) - Doradzińska, Łucja; Wójcik, Michał J.; Paź, Marta; Nowicka, Maria M.; Nowicka, Anna; Bola, Michał
Abstract: The P3 event-related potential has been known for over 50 years, but its function is still a matter of ongoing debate. Current theories interpret P3b either as a correlate of perceptual consciousness, or as reflecting cognitive processes, like working memory and executive functions. Unexpectedly, recent studies indicate that P3b might occur in response to unconsciously presented stimuli which, if further replicated, will be important for defining its functional role. Therefore, in the present study we investigated the P3b component in response to participants' own name - a stimulus which is subjectively extremely salient and known to evoke a robust P3b response. The self-name and control (other) names were presented supra- and subliminally (backward-masked), in a subjective rating task and in a forced-choice identification task. We found that a consciously perceived self-name evoked a P3b of larger amplitude than the other-name in both tasks, which confirms that the self-name was processed preferentially. When the self-name was presented subliminally it was associated with larger P3b amplitude than the other-name in the identification task, but not in the subjective rating task. This indicates that a salient stimulus can in principle modulate the P3b amplitude even when processed outside of awareness, but also that subliminal processing depends on the task-set and top-down factors. Taken as a whole, our results provide evidence against the interpretation of P3b as a correlate of consciousness (and more generally conflict with the Global Workspace Theory) and will allow a more precise description of the relation between P3b and cognitive processes. Highlights: Conscious perception of the self-name evoked larger P3b than other names. Unconscious perception of the self-name also enhanced P3b amplitude. Thus, P3b is not a neural correlate of consciousness (NCC). Unconscious P3b modulation suggests revising its relation with cognitive processes.